Exploring the determinants of FinTech adoption and intention to use in Jordan: The impact of COVID-19 - Ibrahim S. Almashhadani; Mohammad Abuhashesh; Ashraf Bany Mohammad; Ra’ed Masa’deh; Mohammad Al-Khasawneh (Cogent Social Sciences, 2023)
AbstractThis study explores FinTech adoption in Jordan during and post-COVID-19 pandemic by integrating and extending the TAM and UTAUT theories to predict behavioral intention to use FinTech. Six predictors were hypothesized to test their impact on behavioral intention: perceived usefulness, perceived ease of use, social influence, personal innovativeness, financial risks, and privacy risks. while using COVID-19 lockdowns as a moderator. Using structural equation modeling (SEM) on a sample of 296 respondents, the data analysis results indicated that the proposed variables, including the predictors and the moderator, accounted for 38.4% of the variation in behavioral intention to use FinTech. Which clearly shows the important impact of COVID-19 on increasing the adoption of technologies and especially FinTech’s in the Jordanian context. The empirical findings revealed that perceived usefulness and personal innovativeness had the most significant impact on behavioral intention. In contrast, privacy risks had no significant impact on behavioral intention. Besides, this study empirically demonstrated the impact of COVID-19 lockdowns as a moderator. The impact of COVID-19 lockdowns significantly moderated the relationship between perceived usefulness, perceived ease of use, personal innovativeness, and financial risks with behavioral intention. The result of this study contributes to both theory and practice by adding to the existing literature on FinTech adoption using new determinants that might drive behavioral intention to use FinTech services.